Exploring Logistics Strategy in Malaysian SMEs performance - Ramasamy, Ravi; Saifudin, Adam Mohd; Shamsuddin, Jauriyah (International Journal of Supply Chain Management, 2020)
To strengthen the SMEs development, SMEs are measured as one of the essential elements to enhance country economic performance, creating employment opportunities and transforming towards industry by year 2050.Â